Nuclear contamination sources in surface air of Finnish Lapland in 1965–2011 studied by means of 137Cs, 90Sr, and total beta activity - Salminen-Paatero, Susanna; Thölix, Laura E; Kivi, Rigel; Paatero, Jussi (Environmental Science and Pollution Research, 2019)
Radionuclides 137Cs and 90Sr and total beta activity were determined from air filters collected in Rovaniemi (Finnish Lapland) in1965–2011. Nuclear contamination sources present in the air filter samples as well as temporal changes in radionuclide concentrations were examined. Ozone observations and meteorological modeling were used in combination with radionuclide analyses to study the reasons behind the observed seasonal concentration variation. In general, the magnitude and variation in activity concentrations of 137Cs and 90Sr and total beta activity in the surface air of Rovaniemi in 1965–2011 corresponded well with values from other countries. However, the obtained results prove in practice that hardly any refractory or intermediate radionuclides from the destroyed Chernobyl reactor fuel were introduced to Finnish Lapland. The main source of 137Cs and 90Sr and total beta activity in the surface air of Rovaniemi in 1965–2011 has been intense atmospheric nuclear weapon testing in 1950s–1960s and later tests performed in 1965–1980, as well as leakages from underground nuclear tests in Semipalatinsk, 1966, and Novaya Zemlya, 1987. For 137Cs and total beta activity, the influence of Chernobyl and Fukushima accidents was detected. Peer reviewed